Protection of Private Broadcasting Institutions Rights PT. Rajawali Citra Televisi for Television Broadcast Distribution Without Permission - Daniel Zabanax Turnip; Emir Syarif Fatahillah Pakpahan (Syntax Corporation Indonesia, 2022)
In the fourth industrial revolution era, the world is focusing on digital technologies. The development of this technology has forced the Government to meet the needs of all people. Meeting this need requires state intervention that aims to balance the interests of the Creator with the interests of society and the State itself. The interests of the Creator are the protection given by the State to a copyrighted work. This protection is essential to encourage creative people's interest in innovation, which is expected to provide shows that are entertaining, educational, and capable of educating all Indonesian people. This protection also makes a copyrighted work of economic value to every Creator. The problems discussed are how to regulate Copyright in Indonesia, regulate broadcasting rights in Indonesia, and legal protection provided by the Government to related rights to television broadcasts without permission in Decision Number 34/Pdt.Sus-HKI/COPYRIGHT/2019/PN Niaga Jkt.Pst .The research method uses juridical law research methods. This research is a descriptive analysis that reveals. The results of study show that has been done, legal protection of the exclusive rights of creators of phonogram broadcasters seems to have been regulated in Law Number 28 of 2014 concerning Copyright.